POTENSI BAHAYA GEMPA DAN ANALISIS REGANGAN DI SELAT SUNDA BERBASIS GPS (GLOBAL POSITIONING SYSTEM) - Ahmad Fajriyanto; Armijon .; Eko Rahmadi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
The Sunda Strait is the meeting of two tectonic plates, the Eurasian plate and Indo-Australianplate. Sunda Strait has a fairly high seismic activity. This is shown by several earthquakes thathave occurred in the Sunda Strait. The high seismic activity was caused by the presence of activefaults and subduction zones in the Sunda Strait. Based on the fairly high seismic activity in theSunda Strait is necessary to do research on the strain rate that occurred in the Sunda Strait.In thisstudy CGPS observations contained in the Sunda Strait and parts of Java Barat. Based on theresults of GPS data processing, the observation point in the western part of the Sunda Strait hasvelocity in the direction of the North West with a value ranging from 2.21 to 3.16 shift in cm / yearand the eastern part of the Sunda Strait between 2.09 to 3.24 shift cm / year to the Northeast.Based on the pattern of strain, the West tends to have an extension of the Sunda Strait, as well asfor the eastern Sunda Strait. While the northern part of the Sunda Strait compressed. This showsthe activity and the Sumatran Subduction Fault in the area.